2023
DOI: 10.1021/acsenergylett.3c01024
|View full text |Cite
|
Sign up to set email alerts
|

Cationic and Anionic Vacancy Healing for Suppressed Halide Exchange and Phase Segregation in Perovskite Solar Cells

Altaf Pasha,
Patatri Pramanik,
Jesna K George
et al.

Abstract: All-inorganic wide-bandgap (WBG) perovskite solar cells are best suited as the top cells for tandem devices. However, they suffer from photoinduced halide segregation (PIHS) and a quick anion exchange reaction (AER). Herein, polyvinylpyrrolidone (PVP) polymer-assisted in situ crystalization of CsPbBr3 and CsPbBr1.5I1.5 compounds is shown to suppress these effects by passivation of both positively charged (halide vacancy) and negatively charged (cation vacancy) defects. Modifying the perovskite precursor soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…There are several selection criteria for selecting the shell materials, including (1) lattice match with PQDs for epitaxial growth; (2) suitable band alignment with PQDs that facilitates the charge transport; and (3) stable characteristics to protect PQD cores against ambient stimuli like heat, light, moisture, and oxygen. Shelling PQDs with polymers or metal–organic frameworks (MOF) is a good strategy because the soft structure of the shell materials bring not much difficulty for epitaxial growth, and the development of conductive MOF provides opportunities for band alignment between PQDs and MOF. Besides, the chalcogenide perovskites, sharing a similar crystal structure with PQDs, possess outstanding charge mobility and stability, making them promising candidates as a suitable shelling material for PQDs .…”
Section: Yet-to-be-discovered Horizonsmentioning
confidence: 99%
“…There are several selection criteria for selecting the shell materials, including (1) lattice match with PQDs for epitaxial growth; (2) suitable band alignment with PQDs that facilitates the charge transport; and (3) stable characteristics to protect PQD cores against ambient stimuli like heat, light, moisture, and oxygen. Shelling PQDs with polymers or metal–organic frameworks (MOF) is a good strategy because the soft structure of the shell materials bring not much difficulty for epitaxial growth, and the development of conductive MOF provides opportunities for band alignment between PQDs and MOF. Besides, the chalcogenide perovskites, sharing a similar crystal structure with PQDs, possess outstanding charge mobility and stability, making them promising candidates as a suitable shelling material for PQDs .…”
Section: Yet-to-be-discovered Horizonsmentioning
confidence: 99%
“…The device also demonstrated rapid recovery upon removal from a wet environment. Pasha et al utilized PVP polymer to facilitate the in situ crystallization of CsPbBr 3 and CsPbBr 1.5 I 1.5 . The study demonstrated that these compounds could mitigate the effects by passivating positively charged (halide vacancy) and negatively charged (cation vacancy) defects.…”
Section: Application Of Ncps In Pscsmentioning
confidence: 99%
“…36 Kamat and coworkers employed PbSO 4 -oleate capping on perovskite, which effectively inhibits ion exchange. 37 Balakrishna's group inhibited the halide ion exchange in tandem devices via passivating the perovskite's defects using polyvinylpyrrolidone 38 while Santra's group prevented the ion migration at the interfaces of CsPbBr 3 –CsPbI 3 using an ultrathin alumina shell. 39 In this context, utilizing metal chalcogenides for plugging halide vacancies can serve as a potential strategy to prevent the migration of halide ions due to the highly covalent nature of the Pb–chalcogen bond that renders it stable.…”
mentioning
confidence: 99%